2001
DOI: 10.1080/02786820152546752
|View full text |Cite
|
Sign up to set email alerts
|

Wall Loss Rate of Polydispersed Aerosols

Abstract: Wall loss rates of polydispersed aerosols in a stirred vessel were studied theoretically and experimentally. A formula for the polydispersity factor of the wall loss rate was derived using the moment method of log-normal size distribution and compared with numerical calculations. The representative theory of Crump and Seinfeld (1981) was used as the wall loss rate of monodispersed aerosols in which the Brownian diffusion, the turbulent eddy diffusion, and the gravitational settling are included as wall loss me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 15 publications
4
17
0
Order By: Relevance
“…It is therefore possible that any amines present were not suitable for nucleation. Therefore, application of methods capable of amine speciation should be applied more widely in atmospheric measurements (Place et al, 2017). Several CLOUD papers reported particle formation rates for a diameter of 1.7 nm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore possible that any amines present were not suitable for nucleation. Therefore, application of methods capable of amine speciation should be applied more widely in atmospheric measurements (Place et al, 2017). Several CLOUD papers reported particle formation rates for a diameter of 1.7 nm.…”
Section: Discussionmentioning
confidence: 99%
“…2). A weaker size dependence would lead to higher predicted particle concentrations at larger sizes (Park et al, 2001). However, no evidence was found from the existing CLOUD data that this is the case.…”
Section: Size Distribution Comparison Between Model and Smpsmentioning
confidence: 99%
“…Crump and Seinfeld (1981) studied a wall deposition theory of particles in an enclosed vessel explained the motion of aerosol by turbulent transport, Brownian diffusion and gravitational sedimentation. Park, Kim, Han, Kwon, and Lee (2001) investigated the loss rate of polydispersed aerosols from a wall, correcting the model of Crump and Seinfeld (1981) for the polydispersity effects of polydispersed aerosols. Park et al (2001) found that the wall loss rate of polydispersed aerosols exceeded that of monodispersed aerosols.…”
Section: Introductionmentioning
confidence: 99%
“…Park, Kim, Han, Kwon, and Lee (2001) investigated the loss rate of polydispersed aerosols from a wall, correcting the model of Crump and Seinfeld (1981) for the polydispersity effects of polydispersed aerosols. Park et al (2001) found that the wall loss rate of polydispersed aerosols exceeded that of monodispersed aerosols. McMurry and Rader (1985) proposed a wall deposition theory of particles in spherical, electrically charged chambers, for aerosol moved by electrostatic drift, or exhibiting turbulent movement, Brownian diffusion and gravitational sedimentation.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies were conducted in such a way on monodisperse aerosols to determine the deposition rate (Cheng, 1997;Holub, 1984;Morawska & Jamriska, 1996;Mosley et al, 2001;Okuyama, Kousaka, Yamamoto, & Hosokawa, 1986). The deposition of polydisperse suspensions of solid sodium chloride particles and liquid oleic acid droplets was investigated in Park, Kim, Han, Kwon, and Lee (2001) and Kim, Park, Song, Kim, and Lee (2003). The deposition of combustion particles was investigated by Mosley et al (2001) on polydisperse incense particles, and by Jamriska and Morawska (2003) on polydisperse cigarette smoke and petrol smoke.…”
Section: Introductionmentioning
confidence: 99%